The good citizen: Minority and majority youths’ definitions of and experiences with citizenship in Denmark - Bakkær Simonsen, Kristina (Politica, 2021)
Young adults’ abilities and willingness to support and live up to dominant citizen ideals are often questioned, particularly for minority ethnic youths. Based on inductive analysis of 71 interviews, I demonstrate that minority and majority youths share a conception of “the good citizen” as someone who is law-abiding and socially and economically contributing. At the same time, the differential societal status of the two groups affects which of “the good citizen’s” traits and duties they stress, and whether they see themselves as being in a position to make claims to citizenship. While majority youths emphasize political reflection and participation, minority youths place greater weight on not stepping out of line. As such, power and status shape citizenship ideals.